2016
DOI: 10.1097/tp.0000000000001052
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Rich Saline Attenuates Acute Kidney Injury After Liver Transplantation via Activating p53-Mediated Autophagy

Abstract: HRS is able to protect against AKI after liver transplantation partly by reducing apoptosis, which is possibly involved in the modulation of p53-mediated autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…Its diffusion to cellular organelles helps to effectively target intracellular inflammatory factors. Previous studies showed that the inhalation of H 2 exerts protective effects on brain, liver, heart, and intestinal I/R injuries ( Bali et al, 2015 ; Malik and Ferguson, 2015 ; Du et al, 2016 ; Nagpure and Bian, 2016 ). Moreover, H 2 acts as an anti-inflammatory agent in acute pancreatitis, colon inflammation and liver inflammation ( Cheng et al, 2014 ; Yemm et al, 2015 ; Han et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Its diffusion to cellular organelles helps to effectively target intracellular inflammatory factors. Previous studies showed that the inhalation of H 2 exerts protective effects on brain, liver, heart, and intestinal I/R injuries ( Bali et al, 2015 ; Malik and Ferguson, 2015 ; Du et al, 2016 ; Nagpure and Bian, 2016 ). Moreover, H 2 acts as an anti-inflammatory agent in acute pancreatitis, colon inflammation and liver inflammation ( Cheng et al, 2014 ; Yemm et al, 2015 ; Han et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hydrogen-rich saline treatment depressed pro-inflammatory cytokines expression, including IL-6 and IL-1β ( 28 ). In addition, hydrogen-rich saline mediates neuroprotection and attenuates acute kidney injury through the regulation of autophagy ( 29 , 30 ). Oral treatment with hydrogen-rich water for 6 months alleviated the progression of AS in apolipoprotein E-knockout mice ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report in 2007, accumulating evidence has demonstrated its therapeutic potential against IRI and the underlying mechanisms therein. Currently, H 2 is known to have 3 definitive effects: antioxidant, anti‐inflammatory, and antiapoptosis . Though some experimental animal studies have shown its therapeutic potential in organ preservation, eg, lung, heart, kidney, intestine, and liver, its clinical use is yet to be applied because of its unfavorable features.…”
mentioning
confidence: 99%
“…Currently, H 2 i s known to have 3 definitive effects: antioxidant, (5)(6)(7)(8)(9)(10)(11)(12)(13) anti-inflammatory, (10,(14)(15)(16) and antiapoptosis. (8,17) Though some experimental animal studies have shown its therapeutic potential in organ preservation, eg, lung, (11) heart, (18) kidney, (6) intestine, (7) and liver, (19,20) its clinical use is yet to be applied because of its unfavorable features.…”
mentioning
confidence: 99%